Development and usefulness of planning techniques and decision‐making foundations on the example of construction enterprises in Poland - Kapliński, Oleg (Technological and Economic Development of Economy, 2008)
Three groups of planning techniques and foundations for decision‐making techniques have been identified. Their development tendencies have been indicated, as well as degree of practical usage by Polish construction companies. Two periods: the years 1990 and 2005 have been compared. Data and numbers have been obtained mainly by questionnaires and personal contacts. A relationship between the degree of utilisation of the discussed techniques and the type, size, and legal ownership of a construction company has not been found, in spite of current prosperity trends in the construction sector. A discrepancy between the evaluation of the degree of attractiveness of techniques and methods from the viewpoint of academics and building company managers has been pointed out. Planavimo metodai ir sprendimų priėmimo pagrindai Lenkijos statybos įmonėse: naudingumas ir tobulinimas Santrauka. Identifikuotos trys planavimo metodų ir sprendimų priėmimo pagrindų grupės. Nustatytos jų tobulinimo kryptys ir praktinis pritaikymas Lenkijos statybos įmonėse. Palyginti du periodai – 1990 ir 2005 metai. Duomenys surinkti organizuojant apklausas ir naudojantis asmeniniais kontaktais. Nenustatytas ryšys tarp minėtų priemonių naudojimo intensyvumo ir įmonių tipo, dydžio bei teisinio statuso nepaisant dabartinio statybų verslo klestėjimo. Pastebėtas akademinės visuomenės ir statybos kompanijų vadovų nuomonių nesutapimas planavimo priemonių naudojimo ir patrauklumo klausimais. Reikšminiai žodžiai: statybos vadyba, sprendimų priėmimo technika, planavimo priemonės, Lenkija. First published online: 21 Oct 2010